Corrosion protection by organic coatings containing polyaniline salts prepared by oxidative polymerization - Kohl, Miroslav; Kalendová, Andréa; Černošková, Eva; Bláha, Michal; Stejskal, Jaroslav; Erben, Milan (Springer, 2017)
The aim of this work was to describe the polyaniline salts synthesized and to assess the mechanical and anticorrosion properties of alkyd resin-based coating materials pigmented with them, in dependence on the pigment volume concentration (PVC) and type. Polyaniline salts were prepared by oxidative polymerization in the solutions of inorganic (hydrochloric, phosphoric, and sulfuric) and organic (p-toluenesulfonic and 5-sulfosalicylic) acids. Polyaniline salts were characterized by thermal analysis and spectroscopic methods. Electrical conductivity was also measured by the van der Pauw method and the molecular weight of the polyaniline was determined gel permeation chromatography. Furthermore, the particle size of the solid salts was measured and the morphology was studied by scanning electron microscopy. Subsequently, the parameters required to formulate pigmented organic coatings, i.e. density and critical pigment volume concentration were determined. A soybean oil-based fast drying alkyd resin of medium oil length was used as the binder for the organic coating material. Organic coatings containing the polyaniline salts at pigment volume concentrations 0 %, 1 %, 5 %, 10 % and 15 % were formulated and subjected to a standard accelerated cyclic corrosion tests. The organic coatings (paint films) were also subjected to mechanical tests and to the electrochemical test by potentiodynamic polarization studies.
Korozní odolnost organických povlaků s obsahem polyanilinových solí připravených oxidační polymerací.
Keywords: Polyaniline; oxidative polymerization; organic coatings; corrosion.; polyanilin; oxidační polymerace; organický povlak; koroze